Halal Lifestyle in Indonesia: Between Branding, Trends and Needs - Susilawati, Cucu; Dzikrayah, Fithri; Bhatti, Omar Khalid (Universitas Islam Negeri Raden Intan Lampung, 2024)
In Indonesia, the halal lifestyle has begun to be widely implemented by Muslim communities since the government required halal certification for products circulating in Indonesia. However, do Muslim communities implement a halal lifestyle because of their awareness of religious commands, or do they follow trends and are influenced by branding? Therefore, this research aims to determine the influence of branding, trends and needs on implementing halal Lifestyles in daily life by Muslim communities in Indonesia. This research uses a quantitative, descriptive-comparative approach. Data collection techniques were carried out by distributing questionnaires and conducting expert interviews. Questionnaires were distributed to 300 respondents according to the criteria set by the researcher. As a result, the needs variable has the highest score with a total of 4.50 (very strong), while branding gets a score of 4.13 (intense), and the trends variable gets a score of 1.70 (very weak). Based on interviews with experts, the Muslim community in Indonesia agrees and recognizes that a halal lifestyle is not just branding or a trend. However, a halal lifestyle is an obligation that Muslims must carry out according to the commands in the Al-Qur'an and Hadith. For Muslims, adopting a halal lifestyle is worship and is worth a reward. In conclusion, a halal lifestyle is included